An Amazon star is born: Gusmaomyces gen. nov. (Ascomycota incertae sedis) from the Brazilian Amazon - Monteiro, Josiane Santana; Silva, Alexandre Pereira Da; Ferreira, Miriely Cristina Dos Santos; Castañeda-Ruiz, Rafael Felipe (Phytotaxa, 2025)
Gusmamomyces gen. nov. is introduced with two species, G. asteriformis sp. nov. and G. barbarensis sp. nov., collected on living leaflets of Bactris gasipaes and Elaeis guineensis (Arecaceae) in Pará State, Brazil. This genus is characterized by micronematous, hyaline conidiophores, monoblastic conidiogenous cells with percurrent extensions, and staurosporous, pentaradiate or heptaradiate, distoseptate, smooth or verruculose, hyaline conidia with schizolytic secession. A detailed morphological description is provided along with a comparative taxonomic discussion with the closest staurosporous genera. This new genus sheds light on the diversity of palmicolous fungi and shows the importance of fungal taxonomic surveys in the Brazilian Amazon.